Productivity Growth in the Philippines After the Industrial Reforms - Myrna S. Austria (Philippine Institute for Development Studies (PIDS), 1998)
Past studies have shown that Philippine productivity growth has been low compared to other ASEAN members. This is specifically attributed to the inward-looking industrial policies pursued by the government. The country has embarked on major trade reforms since 1980s through its commitment to WTO, AFTA and APEC and in the 1990's through the foreign direct investment (FDI) liberalization. How these affect the country's long-term growth depends on whether the trade reform translates into improvements in productivity. This paper examines the country's productivity performance and analyzes whether or not trade and investment policies have had a significant impact on productivity growth. This also tries to explain changes in total factor productivity (TFP) growth by conducting a regression on TFP against trade and policy indicators.
Keywords: 330; investment opportunities; total factor productivity